A review of gynogenesis manipulation in aquatic animals - Hidayah Manan; A.B. Noor Hidayati; Nur Aina Lyana; Adnan Amin-Safwan; Hongyu Ma; Nor Azman Kasan; Mhd Ikhwanuddin (Aquaculture and Fisheries, 2022)
Gynogenesis is an established technique to generate all female type offspring and this technique has been successfully induced diploid gynogens progeny in aquatic animals of fishes and crustaceans. Monosex culture of all female shrimp and fishes were selected attribute to all female type offspring which have better size than male and help increase the market size and profitable. This article discusses on the protocol applied to produce gynogens progeny and the successful rate of gynogenesis production in fishes, molluscs and aquatic crustaceans of shrimps in general. Overall most of the UV length applied for irradiated the sperm were around 254–365 nm for (20–40 s), (20–80 s) and (5–8 s) for shrimps, 254 nm, 30 s for molluscs species and for fishes were around 254 nm for (1.5min) and (2–12 min) time of exposure respectively. For gynogenesis induction, the fertilized eggs were treated with cold shock, heat shock or cytochalasin- B for both shrimp and fishes gynogens technique. Fertilization rate was identified around 4.33%–19.67% in shrimp. Successful hatching rate was identified around 3.0%, 14.9%–37.2% of gynogens offspring in shrimp and various percentages of hatching rates were identified from each species of fish gynogens. Overall, there is still low survival rate of gynogens produced using gynogenesis technique and further study should be carried out to improve the gynogens production. The discussed protocols serve as a guide lines for the gynogenesis technique application of all female monosex culture in the future.